STUDI MENGENAI PERILAKU PENYESUAIAN DIRI UNTUK MENINGKATKAN KINERJA PENJUALAN (Studi terhadap Tenaga Penjual pada lndustri Asuransi di Kota Semarang) - Sulistiyawati, Erika; Soesanto, Harry (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2003)
In  insurance  industry, salesperson  plays  such  an  important  role  in  promoting  the  product  of insurance. In order to understand that important role.  it  is necessary to understand the characteristics  or abilities required by the sales person to improve  the soles performance.  Even though a salesperson  may have a complement qf adaptive psychological  traits, a lack of communication skill,  indicated by the less ability  of listening will impede success in sales Interactions.  Therefore,  this research proposes a problem whether listening ability could mediate  the relationship between psychological adaptiveness in selling (self monitoring and empathy) and sales performance.  This research aims to analyze the effect of listening ability as mediator in relationship between psychological  adaptiveness in selling  (self-monitoring and empathy) and sales performance.         A model  has been developed  and 5 hypotheses haw  been proposed lo  meet the research problemthrough SEM analysis.  The object of this research Is  the sales person qf insurance  company in Semarang city.  in  which the samples are determined by applying double sampling method,  a combination ofpurposive and quota sampling method.  The sample size  100  insurance sales person and the dala are collected by distributing questionnaires.         The  result  of this  research proved that  all  hypotheses  could  be  accepted,  meaning that self- monitoring and empathy have positive effect on listening ability and sales performance.  also listening ability has positive effect on sales performance,  and able to be explained that self-monitoring and empathy have direct effect on sales performance and might have indirect one,  through listening ability as mediator.